اعتقاد تحريف القرآن عند الشيعة وسببه: Shia’s Belief in the Distortion of Al-Quran and Its Reasons - Muhammad Istiqamah (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
It is said that Shia does not believe in Al-Qur'an that is available today, but we find that the Al-Qur'an that was printed by the Shia is the same Al-Qur'an which is printed elsewhere. Therefore, this study aims to explain the essence of Shia’s belief in Al-Qur'an that is currently in the hands of the Muslims and also the roots of that belief. The method used in this research is descriptive analysis namely by examining classical and modern books particularly the books of Shia’s scholars as the main source to explain and answer the problem formulations in this study. The results of this study indicate that Shia does not believe in Al-Qur'an that exists today. They are forced to read and perform its laws until the emergence of Al-Qaim, which is Imam Mahdi Al-Muntazhar in their version which would carry